Media connection and return comovement - CHEN, Zilin (Institutional Knowledge at Singapore Management University, 2021)
Media news may cover multiple firms in one article, which establishes a media connection across firms. We propose a media connection strength (MCS) measure between two given firms, which is defined as the number of news articles co-mentioning these two firms. We show that the MCS measure can significantly explain and forecast return comovement of media-connected firm-pairs. Further analyses show that our results are robust to various alternative explanations. We argue that the MCS measure can capture comprehensive and complex correlated fundamental information among media-connected firms and hence may provide a new mechanism for return comovement beyond the existing rational- and behavioral-based explanations.